2001
DOI: 10.1354/vp.38-2-129
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Marek's Disease Herpesvirus-induced Lymphoma is Multiphasic and Dependent on Host Genotype

Abstract: Abstract. Genotype-dependent differences in Marek's disease (MD) susceptibility were identified using 14-day-old line N and 6 1 (resistant) and 15I and 7 2 (susceptible) inbred chickens infected with HPRS-16 MD virus (MDV). All line 7 2 chickens developed progressive MD. Line 15I had fluctuating MD-specific clinical signs and individuals recovered. A novel histologic scoring system enabled indices to be calculated for lymphocyte infiltration into nonlymphoid organs. All genotypes had increased mean lesion scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
44
2
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 46 publications
7
44
2
2
Order By: Relevance
“…There is little evidence that MHC-B genotypeassociated differences exist during the initial phase of infection, aside from the slightly delayed appearance of splenomegaly in MHC-B-resistant birds and occasional subtle differences in cytokine profiles [reviewed by (21); see also (22)(23)(24)]. However, by the end of the first 7-10 days post inoculation (dpi), substantial differences in MD pathogenesis become clearly evident.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is little evidence that MHC-B genotypeassociated differences exist during the initial phase of infection, aside from the slightly delayed appearance of splenomegaly in MHC-B-resistant birds and occasional subtle differences in cytokine profiles [reviewed by (21); see also (22)(23)(24)]. However, by the end of the first 7-10 days post inoculation (dpi), substantial differences in MD pathogenesis become clearly evident.…”
Section: Discussionmentioning
confidence: 99%
“…However, by the end of the first 7-10 days post inoculation (dpi), substantial differences in MD pathogenesis become clearly evident. There is an abrupt decrease in the viral load in the white cells in resistant birds (23) that is accompanied by lower levels of infected T cells (25), relatively higher levels of virus-neutralizing antibodies (26), fewer AV37ϩ cells (22), and the absence of induction of the proinflammatory cytokines IL-6 and IL-18, which in contrast occurs in susceptible birds during the same interval (23). In the absence of complicating stress or infection, the genetically resistant birds remain healthy, with the only sign of active infection being the shedding of virus from the feather follicle.…”
Section: Discussionmentioning
confidence: 99%
“…The inbred chicken lines have been selected over many generations for susceptibility (lines 7 2 and 15I) or resistance (lines 6 1 and N) to MD. Fourteen-day-old chickens were infected with HPRS-16 MDV exactly as described previously (14). All animal work was done under and complied with United Kingdom Home Office regulations.…”
Section: Methodsmentioning
confidence: 99%
“…MDV is an accepted and naturally occurring in vivo animal model of herpesvirus oncology (18,30,105), but in common with other animal models, a major impediment to its utility is that the neoplastically transformed cells in MD lymphoma have not been identified. Previous work has suggested that a monoclonal antibody (MAb), AV37, recognizing a novel surface antigen expressed by MDV-transformed cell lines (MDCC) in vitro, identifies the neoplastically transformed cells in MD lymphomas (14,15,85). However, AV37…”
mentioning
confidence: 99%
See 1 more Smart Citation